2008
DOI: 10.2147/vhrm.2008.04.01.189
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and component analysis of metabolic syndrome: An Indian atherosclerosis research study perspective

Abstract: Asian Indians have a high predisposition to metabolic syndrome (MS) and coronary artery disease (CAD). The present study aimed to estimate MS prevalence in 531 Asian Indian families comprising of 2318 individuals. Anthropometrics and lipid profi le were assessed. MS prevalence was estimated using standard Adult Treatment Panel III (ATP-III) and World Health Organisation (WHO) criteria and modifi ed defi nitions which included lowered cut-offs for waist circumference (WC) (Ն90 cm for men and Ն80 cm for women], … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 25 publications
8
40
0
Order By: Relevance
“…However, the small number of samples from affected women precluded any meaningful evaluation of the marker in this group. The average age of the controls were less than that of the CAD patients even though the comparison is probably justified as it has been previously observed by us that these clinical comorbidities such as diabetes, hypertension or metabolic syndrome appear to set in a decade or so earlier than the onset of clinical CAD i.e., around the middle of the fourth decade of life among the IARS cohort (Kanjilal et al 2008). Additionally, the association remained significant even after adjustment for age, gender, diabetes and hypertension implying that the present observations might not be substantially influenced by these covariates.…”
Section: Discussionmentioning
confidence: 92%
“…However, the small number of samples from affected women precluded any meaningful evaluation of the marker in this group. The average age of the controls were less than that of the CAD patients even though the comparison is probably justified as it has been previously observed by us that these clinical comorbidities such as diabetes, hypertension or metabolic syndrome appear to set in a decade or so earlier than the onset of clinical CAD i.e., around the middle of the fourth decade of life among the IARS cohort (Kanjilal et al 2008). Additionally, the association remained significant even after adjustment for age, gender, diabetes and hypertension implying that the present observations might not be substantially influenced by these covariates.…”
Section: Discussionmentioning
confidence: 92%
“…21 According to Snehalata and Ramachandra 22 in Indian population centers have estimated a prevalence of the metabolic syndrome to encompass approximately one-third of individuals residing in large cities. Kanjilal et al 23 have shown in their study that Asian Indians have a high predisposition to metabolic syndrome and coronary artery disease. Roopali Khanna 24 et al in their study, it was seen that metabolic syndrome was common in Indian patients with angiographically documented coronary artery disease.…”
Section: Graph 1 Risk Factorsmentioning
confidence: 97%
“…Studies conducted in India using variable criteria to determine the MetS prevalence showed that in South Indian population, it was 25.8% using IDF as compared to 18.3% by ATPIII, in individuals > 20 years of age [44]. Dissimilar trends were observed in Bangalore, where it was higher using the ATPIII criteria (40.3%) as compared to IDF criteria (34.9%) [18]. Prevalence studies in the rest of the world using different criteria have also demonstrated varying results (Table II).…”
Section: Prevalence Patterns Of Mets In the Developing Worldmentioning
confidence: 97%
“…This rise can be attributed to the transition in the lifestyle from a traditional to a western one. The genesis of MetS and obesity in developing countries relates to demographic transition (shift to low fertility, low mortality, and higher life expectancy), and epidemiological transition (from widely prevalent infectious diseases to a pattern of a high prevalence of lifestyle related diseases) congregating genetics and environment [5,[18][19][20]. The double burden of under and over nutrition in the developing countries is leading to the increased risk for CVD and sequential morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%